Osteocraniostenosis. Issue 10 (October 1994) - Verloes, A; Narcy, F; Grattagliano, B; Delezoide, A L; Guibaud, P; Schaaps, J P; Le Merrer, M; Maroteaux, P
Abstract : We report a multiple congenital anomalies (MCA) syndrome in three unrelated fetuses consisting of extremely thin, dense, fishbone-like diaphyses, flared metaphyses, mild micromelic dwarfism, brachydactyly, facial dysmorphism, ocular malformations (microphthalmia, aniridia), cloverleaf skull deformity, and splenic hypoplasia. Histopathological investigations showed abnormalities of the metaphyseal cartilage and adjacent diaphyseal ossification, excessive modelling of the metaphyses, and, in one case, dysplasia of the epiphyseal cartilage. We review three previously reported cases. We suggest the name osteocraniostenosis to describe this radiological and clinical disorder, pinpointing its major clinical and radiological features.